2016
DOI: 10.5433/1679-0359.2016v37n2p829
|View full text |Cite
|
Sign up to set email alerts
|

Detection of extended spectrum beta-lactamases and resistance in members of the Enterobacteriaceae family isolated from healthy sheep and dogs in Umuarama, Paraná, Brazil

Abstract: Bacterial resistance is a primary public health concern worldwide. Within this context, pets and breeding animals act as reservoirs for multidrug-resistant bacteria (MR), such as those producing extended spectrum beta-lactamases (ESBL) and those presenting plasmid-mediated quinolone resistance (PMQR). The aim of this study was to detect the presence of ESBL and PMQR in members of the Enterobacteriaceae family, isolated from healthy sheep and dogs from non-intense farming rural properties in the Umuarama region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“… Virulence genes Ref. Africa CTX-M-1, CTX-M-15, SHV-12, TEM-135 [ 20 , [111] , [112] , [113] , [114] , [116] , [117] , [118] ] No data America CTX-M-1, CTX-M-2, CTX-M-3, CTX-M-8, CTX-M-9, CTX-M-14, CTX-M-15, CTX-M-24, CTX-M-27, CTX-M-55, CTX-M-65, CTX-M-106, CTX-M-115, CTX-M-123, CTX-M-169, CTX-M-202, SHV-2, SHV-3, SHV-12, TEM-5, TEM-30, TEM-33, TEM-181 [ 10 , 35 , 37 , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] ] afa/draBC, air, cba, cma, cnf1, cvaC, eilA, fimH, focA, fyuA, gad, hlyA, hlyD, ibeA, ipfA, ireA. iroN, iutA, iss, kpsMTII, kpsMTK5, malX, mchF, PAI, papA, papC, papE, papGIII, rfc, sfa/focDE, tsh, traT [ 10 , 21 , 51 , 55 , 56 ] Asia CTX-M-1, CTX-M-2, CTX-M-3, CTX-M-8, CTX-M-9, CTX-M-13, CTX-M-14, CTX-M-15, CTX-M-24, CTX-M-27, CTX-M-28, CTX-M-55, CTX-M-57, CTX-M-64, CTX-M-65, CTX-M-90, CTX-M-104, CTX-M-116, CTX-M-123, CTX-M-127, CTX-M-174, SHV-12, SHV-190, TEM-30 [ 8 , 11 , 13 , 15 , 31 , 36 , [119] , [120] , [121] , ...…”
Section: Resultsmentioning
confidence: 99%
“… Virulence genes Ref. Africa CTX-M-1, CTX-M-15, SHV-12, TEM-135 [ 20 , [111] , [112] , [113] , [114] , [116] , [117] , [118] ] No data America CTX-M-1, CTX-M-2, CTX-M-3, CTX-M-8, CTX-M-9, CTX-M-14, CTX-M-15, CTX-M-24, CTX-M-27, CTX-M-55, CTX-M-65, CTX-M-106, CTX-M-115, CTX-M-123, CTX-M-169, CTX-M-202, SHV-2, SHV-3, SHV-12, TEM-5, TEM-30, TEM-33, TEM-181 [ 10 , 35 , 37 , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] ] afa/draBC, air, cba, cma, cnf1, cvaC, eilA, fimH, focA, fyuA, gad, hlyA, hlyD, ibeA, ipfA, ireA. iroN, iutA, iss, kpsMTII, kpsMTK5, malX, mchF, PAI, papA, papC, papE, papGIII, rfc, sfa/focDE, tsh, traT [ 10 , 21 , 51 , 55 , 56 ] Asia CTX-M-1, CTX-M-2, CTX-M-3, CTX-M-8, CTX-M-9, CTX-M-13, CTX-M-14, CTX-M-15, CTX-M-24, CTX-M-27, CTX-M-28, CTX-M-55, CTX-M-57, CTX-M-64, CTX-M-65, CTX-M-90, CTX-M-104, CTX-M-116, CTX-M-123, CTX-M-127, CTX-M-174, SHV-12, SHV-190, TEM-30 [ 8 , 11 , 13 , 15 , 31 , 36 , [119] , [120] , [121] , ...…”
Section: Resultsmentioning
confidence: 99%
“…This is considered one of the biggest public health problems because infections are common. In some cases, the microorganisms are resistant to the available antimicrobial drugs [10,16,25,26,28].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of the selection of multidrugresistant strains is related to the inappropriate use of antimicrobials, besides their use as growth promotion and prophylaxis, in the case of veterinary medicine. In these cases, the doses of antibiotics used are lower than the therapeutic ones, which facilitate mutations and/or acquisition of resistance genes [4,11,16,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 40.7% E. coli isolation prevalence in this study is higher than 17, 3.2, 24.5, 20, 1.9 and 3% ESBL-resistant/producing E. coli isolation prevalence reported in faecal samples of 53 healthy dogs in Mexico (Rocha-Gracia et al, 2015), oral swabs of 31 healthy dogs in Brazil (Oliveira et al, 2016), faecal samples of 109 healthy dogs in China (Sun et al, 2010), faecal/urine samples of companion animals in Chile (Moreno et al, 2008), 209 dog faecal deposits in Denmark (Damborg et al, 2015) and among 944 clinical E. coli isolates from companion animals in America (Shaheen et al, 2011), respectively. It is also higher than 16, 7, 6.6 and 2.6% ESBL-resistant/producing E. coli isolation prevalence in 100 extra-clinical faecal samples of dogs in Germany (Schaufler et al, 2015), among 445 clinical E. coli isolates from companion animals in United Kingdom (UK) (Timofte et al, 2016), faecal samples of 75 healthy dogs/cats (Costa et al, 2004) and 39 healthy dogs (Costa et al, 2008) reported in Portugal, respectively.…”
Section: Discussionmentioning
confidence: 45%